2016
DOI: 10.1093/jisesa/iew108
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Learned Olfactory Responses in a Wild Population of the Egg ParasitoidTrichogramma(Hymenoptera: Trichogrammatidae)

Abstract: Parasitoid insects face the fundamental problem of finding a suitable host in environments filled with competing stimuli. Many are deft sensors of olfactory cues emitted by other insects and the plants they live on, and use these cues to find hosts. Using olfactory cues from host-plants is effective because plants release volatile organic compounds (VOCs), in response to herbivory or oviposition, that contain information about the presence of hosts. However, plant-produced cues can also be misleading because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Despite overwhelming laboratory-based evidence that parasitoids can learn, few attempts have been made to demonstrate the benefit of learning for optimizing host searching efficacy under (semi)field conditions (but see Gross et al, 1975;Lewis and Martin, 1990;Papaj and Vet, 1990;White and Andow, 2007;Wilson and Woods, 2016;Kruidhof et al, unpublished results). Papaj and Vet (1990) showed that Leptopilina heterotoma females that had experienced the host microhabitat odor in the presence of Drosophila host larvae had a 3-4 times higher chance of finding a host microhabitat than inexperienced females.…”
Section: Effect Of Poc On Parasitoid Host Searching Efficacy In the Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite overwhelming laboratory-based evidence that parasitoids can learn, few attempts have been made to demonstrate the benefit of learning for optimizing host searching efficacy under (semi)field conditions (but see Gross et al, 1975;Lewis and Martin, 1990;Papaj and Vet, 1990;White and Andow, 2007;Wilson and Woods, 2016;Kruidhof et al, unpublished results). Papaj and Vet (1990) showed that Leptopilina heterotoma females that had experienced the host microhabitat odor in the presence of Drosophila host larvae had a 3-4 times higher chance of finding a host microhabitat than inexperienced females.…”
Section: Effect Of Poc On Parasitoid Host Searching Efficacy In the Fmentioning
confidence: 99%
“…The efficacy of parasitoids to find and eliminate pest insects, however, may be constrained by an initially weak response to foraging cues emanating from the crop environment, and/or an innate tendency for dispersal upon release. Learning can greatly enhance the efficacy of parasitoids to locate hosts under field or greenhouse conditions (Gross et al, 1975;Lewis and Martin, 1990;Papaj and Vet, 1990;White and Andow, 2007;Wilson and Woods, 2016). Using so-called "parasitoid olfactory conditioning" (POC from here on; Box 1) Box 1 | De nition of terms used in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Trichogramma spp. can learn volatile plant compounds (Bjorksten and Hoffmann 1995;Pashalidou et al 2010;Wilson and Woods 2016). Recent attempts have been made to use Trichogramma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments on laboratory-reared T. evanescens showed that inexperienced females were not attracted to the synthetic sex pheromone of their hosts, contrary to females with previous oviposition experience (Schöller and Prozell, 2002). If some species of Trichogramma that were reared on factitious hosts were able to respond innately to native host cues (Milonas et al, 2009; Geetha, 2010), previous oviposition experience seems important for responding to olfactory signals (Kaiser et al, 1989; Fatouros et al, 2005; Consoli et al, 2010; Wilson and Woods, 2016). In this study, most EOs elicited escape behaviors in naive laboratory-reared females.…”
Section: Discussionmentioning
confidence: 99%
“…Foraging females can rely on chemical cues coming directly from the host stage they parasitize, such as compounds present on the surface of the eggs (Frenoy et al, 1992; Renou et al, 1992), or signals from different host stages such as larval frass (Rani et al, 2007), wing scales (Lewis et al, 1975; Ananthakrishnan et al, 1991; Fatouros et al, 2005; Milonas et al, 2009) or sex pheromone (Noldus et al, 1990; Frenoy et al, 1992; Boo and Yang, 1998; Geetha, 2010). Trichogramma also exploit chemical signals from the plant emitted either constituvely (Constitutive Volatile Organic Compounds, (Altieri et al, 1982; Romeis et al, 1997; Boo and Yang, 1998; BAI et al, 2011; Wilson and Woods, 2016)) or induced by the presence of hosts such as hosts’ feeding (Herbivore-Induced Plant Volatiles (Peñaflor et al, 2011)) or ovipositing (Oviposition-induced plant volatiles (Fatouros et al, 2005, 2012)) behavior.…”
Section: Introductionmentioning
confidence: 99%